Disparity in judicial decisions in cases of violence against unregistered wives - Omar, Muhammad Rezfah (Priviet Social Sciences Journal, 2026)
Domestic violence can affect anyone; however, wives remain particularly vulnerable to abuse by their husbands. Although Article 2(1)(a) of Law No. 23 of 2004 on the Elimination of Domestic Violence includes husbands, wives, and children within the scope of a household, not all acts of violence against wives are prosecuted under this law. Many legal practitioners still adhere strictly to Article 2 of the 1974 Marriage Law, which considers a marriage valid only if it is conducted according to religious norms and officially registered. This results in perpetrators of violence against unregistered wives being prosecuted under general assault provisions in the Criminal Code rather than under the Domestic Violence Law. This divergence leads to disparities in judicial decisions, arising from differing interpretations of applicable legal provisions, varied judicial reasoning, and the ambiguous legal status of unregistered marriages, complicating consistent legal application. Consequently, similar cases of violence in unregistered marriages can produce inconsistent or even contradictory court rulings. This study highlights several decisions in which courts have applied the Domestic Violence Law to cases involving unregistered wives, with judges determining that the requirement of being within a "household scope" was fulfilled because the parties were married according to religious or customary norms and lived together as husband and wife. This research underscores the importance of recognizing unregistered wives within the household scope, as excluding them results in the denial of essential rights and protections afforded to victims of domestic violence, including access to legal assistance, health services, shelters, and other forms of support.